The C-shaped second mandibular molar and intentional replantation - Bołtacz-Rzepkowska, Elżbieta; Żęcin, Agnieszka; Łęski, Michał (Journal of Stomatology, 2018)
The aim of this case report was to describe the endodontic and surgical treatment of a C-shaped mandibular left second molar. The procedure was performed as re-treatment of an initially failed treatment. During re-treatment, the C-shaped canal was prepared chemo-mechanically and filled. Although clinical and radiological evidence of healing was present after one and two years, the lingual wall of the crown was fractured after five years. The hard tissues were restored with post, core, and porcelain-fused-to-metal (PFM) crown. After three years, clinical examination revealed an 8 mm periodontal pocket in the lingual part of the root, sensation to percussion and tooth mobility. The symptoms suggested root fracture, which required surgical verification. It was decided to perform tooth extraction and intentional replantation if the fracture were not confirmed. The apex was resected and the root end was prepared and filled with mineral trioxide aggregate (MTA). The lingual groove extending from the coronal part of the tooth to the apex was also filled with MTA. The tooth was replanted and splinted with a fiber splint and flow composite for two weeks. The tooth appeared to be clinically asymptomatic after one and two years of the follow-up, and periradicular radiolucency decreased over time. However, signs of ankylosis were observed five years after surgery. In the present case, re-treatment and intentional replantation allowed the tooth to be retained in the oral cavity despite the occurrence of the complication in a form of ankylosis. Sixteen years have passed since the tooth retreatment and 8 years since the procedure of intentional replantation.